Simple and efficient approach to 1,3-aminoalcohols: application to the synthesis of (+)-negamycin - Naidu, S. Vasudeva; Kumar, Pradeep (Tetrahedron Letter, 2007)
A short and practical enantioselective synthesis of (+)-negamycin has been achieved in high enantio- and diastereomeric excess using an iterative Jacobsen's hydrolytic kinetic resolution as the key step. (C) 2007 Elsevier Ltd. All rights reserved.

Synthesis of alpha-amino phosphonates by three component condensation of carbonyl compound, amine, and dialkyl phosphite using Yttria-zirconia based Lewis acid catalyst - Ramalingam, S.; Kumar, Pradeep (Catalysis Letters, 2008)
An efficient Yttria-zirconia Lewis acid catalyzed one-pot synthesis of alpha-amino phosphonates by three component coupling reaction of a carbonyl compound amine and dialkyl phosphates is described in good to high yield.
Keywords: alpha-amino phosphonates; three component coupling; Yttria-zirconia based Lewis acid catalyst

Synthesis of chiral sulfoxides by enantioselective sulfide oxidation and subsequent oxidative kinetic resolution using immobilized Ti-binol complex - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2009)
Chiral Ti-binol complex was immobilized onto ionic liquid modified SBA-15 and characterized by different physicochemical techniques. The catalyst was found to be highly enantioselective in the heterogeneous asymmetric oxidation of prochiral sulfides to sulfoxides and subsequent oxidative kinetic resolution of the sulfoxides using aqueous tert-butylhydroperoxide as the oxidant. A positive non-linear effect was observed in the oxidation-kinetic resolution of thioanisole using this supported catalyst. The supported catalyst was reused in multiple catalytic runs without any loss of enantioselectivity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Kinetic resolution; Mesoporous silica; Non-linear effect; Sulfides; Sulfoxides; Supported ionic liquid; Ti-binol

Short and efficient synthesis of (S)-(+)-2-(Hydroxymethyl)-6-piperidin-2-one - Upadhyay, Puspesh K.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A concise synthesis of (S)-(+)-2-(hydroxymethyl)-6-piperidin-2-one is described that employs L-aspartic acid as chiral pool starting material and Wittig reaction as the key step.
Keywords: Amino acid; Hydrogenation; L-aspartic acid; pipecolate; piperidone; Wittig reaction

Synthesis of aculeatins A and B via iterative hydrolytic kinetic resolution - Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A simple and concise approach for the synthesis of aculeatins A and B starting from (+/-)-epichlorohydrin is described. The synthetic strategy features Jacobsen's hydrolytic kinetic resolution and a Linchpin coupling as key steps.
Keywords: aculeatins; Epoxide; Hydrolytic kinetic resolution; Linchpin coupling; spirocyclization

Synthesis of (-)-galantinic acid via iterative hydrolytic kinetic resolution and tethered aminohydroxylation - Dubey, Abhishek; Kauloorkar, Shruti Vandana; Kumar, Pradeep (Tetrahedron, 2010)
A new synthetic strategy for (-)-galantinic acid is reported using iterative hydrolytic kinetic resolution and tethered aminohydroxylation as the key steps. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-Aminoalcohol; 3-Diol; Iterative hydrolytic kinetic resolution; selectivity; Tethered aminohydroxylation

Synthesis of (R)-coniine and (S)-coinicine via organocatalytic alpha-aminoxylation of an aldehyde - Kondekar, Nagendra B.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A short and efficient synthesis of the indolizidine alkaloid (S)-coinicine has been achieved using organocatalytic sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of an aldehyde catalyzed by L-proline. Similarly, a common organocatalytic alpha-aminoxylation route has been developed for the asymmetric synthesis of both (R)-coniine and (S)-coinicine.
Keywords: hemlock alkaloids; organocatalysis; Proline; sequential reactions; synthesis

Stereoselective synthesis of (-)-galantinic acid - Dubey, Abhishek; Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2011)
An efficient and highly concise synthesis of (-)-galantinic acid has been achieved using an asymmetric allylation reaction of Garner's aldehyde.
Keywords: Amino alcohol; Chiral pool; iterative asymmetric allylation; Oxidation; stereoselective synthesis

Stereoselective synthesis of ophiocerins A and C - Show, Krishanu; Gupta, Priti; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
An efficient synthesis of ophiocerins A and C has been achieved via a common intermediate. The stereogenic centers were generated by means of Jacobsen's hydrolytic kinetic resolution and Sharpless kinetic resolution. (C) 2011 Elsevier Ltd. All rights reserved.

Synthesis of (R)-selegiline via hydrolytic kinetic resolution - Kondekar, Nagendra B.; Kumar, Pradeep (Synthetic Communications, 2011)
[image omitted] A short and enantioselective formal synthesis of (R)-selegiline has been achieved using Jacobsen's hydrolytic kinetic resolution (HKR) of phenyl propylene oxide.
Keywords: Cobalt-based chiral salen complex; Hydrolytic kinetic resolution; MAO inhibitors; phenyl propylene oxide; selegiline

Synthesis of indolizidine, pyrrolizidine and quinolizidine ring systems by proline-catalyzed sequential alpha-amination and HWE olefination of an aldehyde - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Kumar, Pradeep (RSC Advances, 2013)
A general procedure for the synthesis of azabicyclic ring systems viz. indolizidine, pyrrolizidine and quinolizidine has been developed utilizing proline-catalyzed sequential alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of an aldehyde as the key step. This method can be further extended to the synthesis of various biologically active natural products containing azabicyclic ring systems.

Stereoselective approach to 2,6-disubstituted piperidin-3-ol: synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline - Jha, Vishwajeet; Kauloorkar, Shruti Vandana; Kumar, Pradeep (European Journal of Organic Chemistry, 2014)
A simple and highly efficient approach to an enantioenriched 2,6-disubstituted piperidin-3-ol skeleton is developed from an aldehyde as a starting material by using organocatalytic and asymmetric dihydroxylation as the key steps. Its application to the total synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline is also reported.
Keywords: alkaloids; Amination; Amino alcohols; synthetic methods; Wittig reactions

Stereoselective approach to indolizidine and pyrrolizidine alkaloids: total synthesis of (-)-lentiginosine, (-)-epi-lentiginosine and (-)-dihydroxypyrrolizidine - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Jogdand, Ganesh F.; Kumar, Pradeep (Organic & Biomolecular Chemistry, 2014)
A simple and highly efficient approach to hydroxylated pyrrolizidine and indolizidine is developed from an aldehyde as a starting material using organocatalytic and asymmetric dihydroxylation reactions as key steps. Its application to the total synthesis of (-)-lentiginosine, (-)-epi-1,2-lentiginosine and (-)-dihydroxypyrrolizidine is also reported.

Stereocontrolled synthesis of Hagen's gland lactones via iterative proline catalyzed alpha-aminoxylation and oxa-Michael addition reactions - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Jogdand, Ganesh F.; Kumar, Pradeep (RSC Advances, 2015)
A simple and efficient synthesis of Hagen's gland lactones was achieved using a sequential alpha-aminoxylation/oxa-Michael approach in a highly diastereoselective manner with assignment of relative configurations. This method was found to be applicable to the synthesis of various other isomers of Hagen's gland lactones.

Synthesis of ophiocerins A, B and C, botryolide E, decarestrictine O, stagonolide C and 9-epi-stagonolide C employing chiral hexane-1,2,3,5-tetraol derivatives as building blocks - Show, Krishanu; Kumar, Pradeep (European Journal of Organic Chemistry, 2016)
An organocatalytic approach to the synthesis of (2R,3S)-hexane-1,2,3,5-tetraol (11) derivatives (in the forms of different stereoisomers and bearing different protecting groups) has been developed. The key chiral intermediates 11 were prepared with complete stereocontrol through the proline-catalyzed intermolecular aldol reaction between acetone and d-glyceraldehyde acetonide. The synthetic utility of the intermediates was demonstrated by their transformation into the title hydroxylated pyrans and a variety of unsaturated lactones through standard synthetic protocols.

Synthesis of heterogeneous Ru(II)-1,2,3-triazole catalyst supported over SBA-15: application to the hydrogen transfer reaction and unusual highly selective 1,4-disubstituted triazole formation via multicomponent click reaction - Sharma, Priti; Rathod, Jayant; Singh, A. P.; Kumar, Pradeep; Sasson, Yoel (Catalysis Science & Technology, 2018)
In the present study, we demonstrate a simple and efficient method for ligand formation and covalent anchoring to a heterogeneous support via click reaction. The complex tris(triphenylphosphine) ruthenium(II) dichloride [RuCl2(PPh3)(3)] anchored over the click modified ligand of SBA-15 forms a new highly efficient heterogeneous SBA-15-Tz-Ru(II) TPP catalyst. Solid state C-13, Si-29, and P-31 CP-MAS NMR spectra provide evidence for the formation of the heterogeneous catalyst. SBA-15-Tz-Ru(II) TPP catalyst was screened for the multicomponent click cycloaddition reaction in water medium as a green solvent and it exhibited unusual and excellent selectivity for the formation of 1,4-disubstituted triazole product under mild reaction condition. In addition, SBA-15-Tz-Ru(II) TPP catalyst also catalyzed the hydrogen transfer reaction of various carbonyl compounds with excellent catalytic activity to give the corresponding alcohols. The heterogeneous catalyst can be recycled and reused several times (five) without a loss in reactivity.